2016
DOI: 10.1371/journal.pone.0150422
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from Congenital Heart Disease in Mexico: A Problem on the Rise

Abstract: Background and ObjectivesTemporal trends in mortality from congenital heart disease (CHD) vary among regions. It is therefore necessary to study this problem in each country. In Mexico, congenital anomalies were responsible for 24% of infant mortality in 2013 and CHD represented 55% of total deaths from congenital anomalies among children under 1 year of age. The objectives of this study were to analyze the trends in infant mortality from CHD in Mexico (1998 to 2013), its specific causes, age at death and asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 21 publications
1
29
0
10
Order By: Relevance
“…Diabetes and substance abuse, both known to be associated with CHD, are more prevalent now in women of reproductive age than 10 years ago. In addition, the number of specialists per capita has increased in recent years; therefore, it is possible that deaths from CHD that were not previously detected are now diagnosed and recorded as causes of infant mortality …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Diabetes and substance abuse, both known to be associated with CHD, are more prevalent now in women of reproductive age than 10 years ago. In addition, the number of specialists per capita has increased in recent years; therefore, it is possible that deaths from CHD that were not previously detected are now diagnosed and recorded as causes of infant mortality …”
Section: Discussionmentioning
confidence: 99%
“…In other studies, conducted in Mexico, very similar results have been found in children <1 year of age. In the year 2013, it was seen that out of the four regions (North, South, Center, and Mexico City), Mexico City had the highest mortality rate with 188.5 per 100 000 live births, which could be due to genetic or environmental factors, or to underreporting of deaths in states with fewer resources . The obesity epidemic with phenotypes associated with diabetes mellitus and hypercholesterolemia are considered as emerging risk factors for CHD .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations